Conditions necessary for effective prevention of cardiovascular and other non-communicable disease in the Russian Federation - R. G. Oganov; G. Ya. Maslennikova; I. E. Koltunov; A. M. Kalinina (Кардиоваскулярная терапия и профилактика, 2010)
.